Structural transitions in a NiTi alloy: a multistage loading-unload cycle - V. Di Cocco; C. Maletta; S. Natali (Fracture and Structural Integrity)
NiTi shape memory alloys (SMAs) are increasingly used in many engineering and medical applications, because they combine special functional properties, such as shape memory effect and pseudoelasticity, with good mechanical strength and biocompatibility. However, the microstructural changes associated with these functional properties are not yet completely known. In this work a NiTi pseudo-elastic alloy was investigated by means of X-ray diffraction in order to assess micro-structural transformations under mechanical uniaxial deformation. The structure after complete shape recovery have been compared with initial state.